ICT정부조직 비교연구 - 차성민(Seong-Min Cha) (한국비교정부학보, 2012)
Korean government has been evaluated as the most successful government in establishing and implementing of ICT industrial policy. In the era of mobile-centric smart-phone, however, the environment of korean ICT industry is getting in crisis recently. In this circumstance, it is important to establish the ICT governmental organization in order to provide incentives to invest in network for enhancing the ICT industry as the mobile internet market revitalization and new service creation through convergence of broadcasting and telecommunications. In this paper, for the rebirth of the ICT industry in Korea, I propose to present a model of effective ICT policy organizations. For this purpose, I have looked into ICT agencies of 9 major countries overseas broadcasting and telecommunications policy in the field of information and telecommunications. I divided overseas cases into two criteria. And then, on the basis of research results, I drew some implications for efficient ICT reorganization. In conclusion, it is important to install ICT dedicated organizations which can implement promotion policy and regulatory policy of the broadcasting and telecommunications industry in the mid-term to long-term. Especially, it would be desirable to establish regulatory agency separately, because political independence and neutrality must be guaranteed in the field of regulatory affairs. KCI Citation Count: 4